Risk and protective factors in boys/girls and adolescents in poverty in educational institution of Villa El Salvador - Deza Villanueva, Sabina Lila (2015)
This work is an investigation of some risk and protective factors present in a sample of 300 boys / girls and adolescents in poverty, studying in educational institutions of Villa El Salvador. It was developed together with the students of the third year of the career of Psychology, Department of Psychology of the Community in the context of an agreement with the Parish Christ bran VES, to provide this help people spiritually and psychologically. We used qualitative methodology through in-depth interviews, participant observation and group dynamics.It was identified that the own shortcomings of poverty constitute permanent stressors that affect family dynamics and relationships. Which results in weakening the role of support, protection and guidance needed by children and adolescents from their family and the presence of adults with positive attitudes who are role models for their proper development.